Nemesis [large type] - Pronzini, Bill (Pronzini, Bill. "Nameless Detective" mysteries., 2013)
Agreeing to investigate threats by a mysterious extortionist against a newly rich young woman, Jake Runyon makes a series of surprise discoveries that cause him to be wrongfully accused of a crime and his employers to be subjected to a vicious legal vendetta--Publisher.